Isolation, molecular profiling, and antimicrobial sensitivity patterns of ESBL producing Acinetobacter baumannii in wastewater discharges from Goranchatbari sub-catchment area in Dhaka - Amanta Rahman; Nayeema Haque; Mohammed Tanveer Hussain; Md. Sakib Hossain; Ahmed Ishtiaque Amin Chowdhury; Md. Foysal Abedin; Tahani Tabassum; Md. Hajbiur Rahman; Mohammad Atique Ul Alam; Mohammad Rafiqul Islam; Iftekhar Bin Naser; Md. Shafiqul Islam; et al. (PLoS ONE, 2026)
The World Health Organization has recommended the development of new antimicrobials against Acinetobacter baumannii , one of the six highly significant pathogens. In this study, 28 wastewater samples were collected from the Goranchatbari sub-catchment area in Dhaka city over several periods. The samples were characterized for the presence of Acinetobacter spp. The isolates showing cream, opaque colonies on CHROMagar TM ESBL plates were considered positive for ESBL production. They were further characterized for major antibiotic resistance and pathogenic genes, biofilm production and antibiotic susceptibility testing. Furthermore, the isolates were phylogenetically clustered based on their Enterobacterial Repetitive Intergenic Consensus (ERIC) profiles and correlation matrix analysis was performed. Out of 28 samples, 27 were positive for Acinetobacter spp. and a total of 106/249 (42.6%) sample representative isolates were positive for ESBL production. Out of these 106 isolates, 97 (91.5%) were genotypically confirmed to belong to the Acinetobacter spp . and of which, 72 (74.2%) were genotypically confirmed as Acinetobacter baumannii . Among the distribution of β-lactamase genes, bla TEM was the most prevalent being present in 40/72 (55.6%) isolates, followed by bla SHV in 3/72 (4.2%) isolates. With respect to the pathogenic genes, pgaB and bfmS were the most prevalent being present in 80.6% and 69.4% of the isolates, respectively. The antibiotic susceptibility testing revealed a diverse range of resistance patterns with high levels of intermediate resistance being observed for cefotaxime and ceftriaxone. The biofilm formation screening revealed that 48.6% and 44.4% of isolates formed strong biofilms at 37°C and 25°C, respectively. The phylogenetic clustering of the A. baumannii isolates resulted in the formation of 10 clusters at 60% similarity index, and the correlation matrix helped reveal important associations between genotypic and phenotypic traits. These results demonstrate the continued prevalence of A. baumannii within these environmental reservoirs and its ability to persist despite seasonal variations, prioritizing changes in environmental health policies that aim to reduce the widespread prevalence of these pathogens.